Clinical nutrition counselling service in the veterinary hospital: retrospective analysis of equine patients and nutritional considerations. (19th June 2017) - Vergnano, D.; Bergero, D.; Valle, E.
Summary: Nutrition plays a very important role in the healthy and in the ill horse. Although research in this field clearly shows that incorrect nutritional practices may lead to severe pathologies, inappropriate feeding plans often continue to be used. A clinical nutrition counselling (CNC) service could thus be of great use to both horse owners and veterinarians. The aim of this study was to provide information on equine patients referred to the CNC service of the University of Turin and to provide standard dietary protocols as used in our Veterinary Teaching Hospital for the most common nutrition‐related pathologies. The data were obtained by retrospective analysis of the nutritional records of referred equine patients. The data collected included information about anamnesis, nutritional assessment, current diet, referring person and follow‐up of each patient. Sixty‐one horses were included in the study. The majority were adult males. The most common breeds were the Italian Saddle Horse and the Friesian Horse. Old horses (>19 years) had a statistically lower BCS than brood mares or other adult horses (p < 0.01). The most common nutritional pathologies were chronic weight loss (CWL), chronic diarrhoea (CD) and equine gastric ulcer syndrome. All horses received first‐cut meadow hay; 85% also ate concentrates. Young horses (<2 years) received more hay as a percentage of body weight (BW) than old horses or adults. The hay percentage of BW per day given to animals with CWL was statistically higher than those with CD (p < 0.01). The concentrate percentage of BW given to old horses was statistically lower compared to that given to young horses (p < 0.05). The concentrate percentage of BW per day given to horses with colic was statistically higher than that given to horses with CD (p < 0.05). 28% of cases were referred by the owner and 72% by a veterinarian. Follow‐up evaluation was deemed to be 'good' in 92% cases and 'poor' in 8%. In summary, the CNC service could provide an epidemiological observatory to study the prevalence of nutritional issues in the equine population.